Processing Agroindustry By-Products for Obtaining Value-Added Products and Reducing Environmental Impact - Iván Almaraz-Sánchez; Aldo Amaro-Reyes; Jorge Alberto Acosta-Gallegos; Magdalena Mendoza-Sánchez (Journal of Chemistry)
Over four billion tons of foods are produced annually on the planet, and about a third is wasted. A minimal part of this waste is incinerated or sent to landfills for treatment, avoiding contamination and diseases; the rest is disposed of elsewhere. The current review was aimed at broadening the panorama on the potential of agroindustrial by-products in applications such as biofuels, biomaterials, biocompounds, pharmaceuticals, and food ingredients. It also exposes the main chemical, physical, and biochemical treatments for converting by-products into raw materials with added value through low environmental impact processes. The value of agroindustrial waste is limited due to the scarce information available. There is a need for further research in unexplored areas to find ways of adding value to these by-products and minimizing their contamination. Instead of throwing away or burning by-products, they can be transformed into useful materials such as polymers, fuels, antioxidants, phenols, and lipids, which will effectively reduce food waste and environmental impact.